Neutron capture reaction cross-section of 79Se through the 79Se(d,p) reaction in inverse kinematics - N. Imai; M. Dozono; S. Michimasa; T. Sumikama; S. Ota; S. Hayakawa; J.W. Hwang; K. Iribe; C. Iwamoto; S. Kawase; K. Kawata; N. Kitamura; et al. (Physics Letters B, 2024)
γ emission probabilities from unbound states in 78,80Se, populated by a neutron-transfer reaction (d,p) on 77,79Se nuclei in inverse kinematics, were measured by directly detecting reaction residues. Assuming the spin distribution at the respective excitation energy of the unbound state, the cross-sections of the 79Se(n,γ)80Se reaction were evaluated using the γ emission probabilities. The surrogate-ratio method with the experimental γ emission probabilities of 78,80Se was also employed to deduce the cross-sections of 79Se(n,γ) reaction by incorporating the theoretical evaluations of the neutron-capture reaction on the isomeric state in 77Se. Our two cross-sections are in good agreement with existing nuclear data compilations for the neutron-capture reaction on 79Se. The presented method contributes to the body of existing knowledge by providing approaches for determining the neutron capture cross-sections of radioactive nuclei at various neutron energies.